Small funding can make a big difference: short-term outcomes of five projects linking livelihoods with mental health and well-being in torture-survivors - Soley, Berta; Park, Skyla (Torture Journal, 2024)
Half of all survivors of torture (SOT) worldwide live in poverty. When treating SOT, rehabilitation and mental health treatment cannot be expected to work independent from supplemental support (specifically livelihoods) ensuring that individuals’ most basic needs are met (Mukwege and Berg, 2016; Patel, 2019). It is said that rehabilitating SOT without livelihoods support is comparable to “a car without wheels.” For instance, a doctor may inform a patient that they must eat prior to taking their medications, unknowing of the patient’s lack of reliable access to food. Or, a SOT may attend weekly sessions for counselling to no avail as they return to a home without sufficient food for the family— another stressor deterring focus from rehabilitation.